Aplikasi Forecasting Supplier Sembako Dengan Metode Least Square Dan Double Exponential Smoothing - Andrean, David; Susanto, Revin; Hakim, Lukman (LPPM UNIKA Santo Thomas, 2021)
Groceries suppliers can operate in the trading sector. However, the problem experienced by suppliers is that it is difficult to predict the groceries stock needed in the next period, besides that there are certain limitations in predicting the groceries stock. Seeing these problems, it is necessary to build a forecasting application for groceries stock with the least square and double exponential smoothing methods which aim to solve problems with groceries suppliers. Kata kunci—Supplier Sembako, Metode Least Square, Metode Double Exponential Smoothing